2019
DOI: 10.1101/589424
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiomics Analysis of the mdx/mTR Mouse Model of Duchenne Muscular Dystrophy

Abstract: Duchenne muscular dystrophy (DMD) is a progressive neuromuscular disease characterized by extensive muscle weakness. Patients with DMD lack a functional dystrophin protein, which transmits force and organizes the cytoskeleton of skeletal muscle. Multiomic studies evaluate combined changes in the transcriptome, proteome, and metabolome, and have been proposed as a way to obtain novel insight about disease processes from preclinical models.We therefore sought to use this approach to study pathological changes in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…We compared the transcriptomic analyses of ΔEx51 muscle with the mdx/mTR muscle published previously (18) and observed overlap between differentially expressed genes between these two models (SI Appendix, Fig. S2 C and D).…”
Section: Resultsmentioning
confidence: 98%
“…We compared the transcriptomic analyses of ΔEx51 muscle with the mdx/mTR muscle published previously (18) and observed overlap between differentially expressed genes between these two models (SI Appendix, Fig. S2 C and D).…”
Section: Resultsmentioning
confidence: 98%
“…Its expression was not altered by the presence of the defects, which is not in favor of a potential role in their establishment. However, recent results showed that adiponectin content may change following posttranscriptional regulation (Van Pelt et al, 2020).…”
Section: Pathways Involved In Muscle Metabolism and Contractile Functionmentioning
confidence: 99%
“…Besides systematic transcriptomic surveys [190,306] and metabolomic research [60,178,345] in the field of dystrophinopathy, a major area of omics-based biomarker discovery employs mass spectrometric and proteomic screening protocols for the large-scale identification of new peptides, protein fragments and protein biomarker candidates [42,82]. A few studies have also used multi-omics approaches for studying dystrophic changes at the various levels of biological organisation from gene to mRNA to protein expression [122,224,352]. The integration of genomics and proteomics for the in-depth proteogenomic characterisation of rare neuromuscular disorders is an attractive approach that combines advanced proteomic screening with gene discovery [279].…”
Section: Novel Proteomic Biomarkers Of the Complex Aetiology Of Duchenne Muscular Dystrophymentioning
confidence: 99%